Direct measurement of lower thermospheric neutral density using multifrequency incoherent scattering. Issue 23 (1st December 2014) - Nicolls, Michael J.; Bahcivan, Hasan; Häggström, Ingemar; Rietveld, Michael
Abstract: Incoherent scatter (IS) is sensitive to collisional properties of the ion gas when the mean free path is close to the radar wave number. However, it has been traditionally difficult to infer the rate of collisions from IS measurements because of ambiguities in the theory for measurements at a single wave number ( k ). We demonstrate that multifrequency measurements to achieve diversity in k can allow for direct inference of the composition‐weighted ion‐neutral collision frequency in the upper mesosphere and lower thermosphere. By direct, we mean that no significant constraints are imposed on the interpretation of the IS spectra and that interpretation relies only on the IS formalism (rather than a steady state ion‐momentum equation, for example). The technique is demonstrated using measurements from the European Incoherent Scatter VHF and UHF radar systems. This technique can be used to investigate neutral atmosphere variations as well as the validity of collision models commonly used in the IS formalism. Key Points: IS is sensitive to collisions when the mean free path is close to the wave number Multifrequency measurements allow for direct inference of collision frequency Can be used to investigate neutral atmosphere and collision models